Traditional eye treatments amongst patients consulting at eye clinic at the Letaba Regional Hospital, Limpopo Province of South Africa - Rakoma, Tumelo Florence (University of Limpopo, 2017)
The title of the study: Traditional eye care treatments amongst patients consulting at Eye Clinic, at the Letaba Regional Hospital, Limpopo Province of South Africa. Background: The use of traditional eye medicine (TEM) is increasingly widespread across the world. TEM use can be described as damaging or harmless depending on the type of substances used. These may include instillation of plant or animal blends into the eyes. The treatment may introduce infection to the already damaged eye or cause irreversible blindness. Most of the previous studies associated the use of TEM with poor visual outcome on the eye. These complications may worsen the burden of blindness. The study will provide eye care practitioners with information on awareness and education regarding the effects of traditional eye medicine. It will assist the authorities in the collaboration of traditional medicine (TM) and the western health system. Objectives: To describe traditional eye medicine, the prevalence of use and the treatment outcome among patients consulting the Eye Clinic, at the Letaba Regional Hospital. Methodology: The study design used is quantitative cross sectional. The researcher employed convenient sampling. A total of hundred patients participated in the study, every patient coming to the clinic was considered until the sample size of 100 was reached. The data was collected using a structured self - administered questionnaire as a tool. The demographic characteristics included age, gender, the level of education, distance between health facility and home. Results: The study comprised of 59% of females and 41% were males. The study showed that 22 out of 36 (61.1%) females and 14 out of 36 (38.9%) of males used TEM the most. The respondents aged between 50 – 60 years were the most users of TEM. The prevalence of TEM use was found to be 36% among the participants. The most frequently experienced symptoms among the respondents was pain at 34.3% while the most-commonly used TEM was sugar and water solution followed by herbal mixtures. The study showed that 49% of the study participants thought TEM is inexpensive and 44% reported that hospitals are too far away. Relationships were measured using Chi-square (p-value < 0.05) between the variables and the following associations were found: type of eye medicine used and religion of the participants (p = 0.03); Type of eye medicine used in the past and eye symptoms commonly experienced (p = 0.01); Type of eye medicine used and treatment benefits (p = 0.01); sources of information on eye health and type of eye medicine sought in the past (p = 0.01). v Conclusion: TEM is commonly used in communities consulting at the Letaba Regional Hospital even though the treatment outcome is generally not beneficial. Awareness should focus more on promoting good eye health in order to prevent blindness. The Department of Health and communities should be made aware of the harmful effects of traditional remedies. Since the effects of traditional medicine are not documented it is important that more research be conducted in order to promote the best eye care treatments and discourage the harmful practices of TEM. Keywords: Treatment outcome, Blindness, Awareness
Thesis (M.PH) --University of Limpopo, 2017
Keywords: Treatment outcome; Blindness; Traditional eye medicine; Eye| - Diseases - Homeopathic treatment.; Traditional medicine - South Africa.